A comparison of computational methods to determine intrastroke velocity in swimming using IMUs - Worsey, M. T. O.; Pahl, R.; Thiel, D. V.; Milburn, P. D. (IEEE Sensors Letters, 2018)
Sacrum located IMU sensors were used to monitor three-axis acceleration and three-axis rotation from elite swimmers in competition conditions. The intrastroke velocity was determined for each swimmer using their preferred swim stroke (freestyle, backstroke, and breaststroke) using three different calculation techniques-dual-axis acceleration, dualaxis acceleration eliminating the static gravity constant, and altitude and heading reference system. The mean intrastroke velocity variation (averaged over one 50-m lap) in freestyle swimming was less than 0.6% in all cases. This resulted in a timing under-estimate of less than 0.60 ms for freestyle, 4.0 ms for breaststroke, and a timing overestimate of less than 6.2 ms for backstroke. The difference was less than 5% over the complete stroke (one way ANOVA p > 0.05), indicating no significant difference in the velocity profiles. These simple, robust analysis techniques can be used to quantify variations in every stroke as the swimmer fatigues, providing significant information to coaching staff and athletes.